Taxonomic and nomenclatural novelties in Leucoagaricus (Agaricaceae) from Brazil - Heisecke, Celeste; Barbosa, Jaime Andrés Duque; Neves, Maria Alice; Carvalho Jr, Anibal Alves De (Phytotaxa, 2021)
Leucoagaricus nzumbae sp. nov. (Agaricaceae) is described based on morphological and molecular data from Teresópolis, Rio de Janeiro, Brazil. This species is characterized by the delicate small basidiomes that turn completely lilac when dried, brownish color of the pileus surface, and trichodermal elements with intracellular and parietal brown pigments of the pileus covering. A lectotype and an epitype are designated for Leucoagaricus gongylophorus, a symbiotic fungus of leaf-cutting ants. Full description, nomenclatural notes, and illustrations of fresh basidiomes in situ and of the main macro-and micromorphological features of both species are provided.